On Computation of Face Index of Certain Nanotubes. (16th July 2020) - Ye, Ansheng; Javed, Aisha; Jamil, Muhammad Kamran; Abdul Sattar, Kanza; Aslam, Adnan; Iqbal, Zahid; Fahad, Asfand
Abstract : Topological index is a number that can be used to characterize the graph of a molecule. Topological indices describe the physical, chemical, and biological properties of a chemical structure. In this paper, we derive the analytical closed formulas of face index of some planar molecular structures such as TUC 4, TUC 4 C 8 S, TUH C 6, TUC 4 C 8 R, and armchair TUV C 6 .